Trichloroethylene (Geneva, 1985)
"Trichloroethylene is a liquid with extensive applications in metal degreasing, textile cleaning, solvent extraction processes, and as a carrier solvent. Exposure in the workplace, which may occur via inhalation of the vapour or skin contamination with the liquid, is known to carry risks of central nervous system disturbances and liver and kidney damage. This report provides a thorough assessment of the risks to human health and the environment posed by the industrial use of trichloroethylene. Information ranges from a survey of analytical methods for assessing levels in human tissues and fluids, through a list of signs and symptoms of over-exposure in man and the treatment of poisoning, to a statement of precautions to follow in handling, storage, and disposal."